The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1073/pnas.95.12.6959
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-2 induces β2-integrin-dependent signal transduction involving the focal adhesion kinase-related protein B (fakB)

Abstract: ABSTRACT␤ 2 integrin molecules are involved in a multitude of cellular events, including adhesion, migration, and cellular activation. Here, we studied the inf luence of ␤ 2 integrins on interleukin-2 (IL-2)-mediated signal transduction in human CD4؉ T cell lines obtained from healthy donors and a leukocyte adhesion deficiency (LAD) patient. We show that IL-2 induces tyrosine phosphorylation of a 125-kDa protein and homotypic adhesion in ␤ 2 integrin (CD18)-positive but not in ␤ 2 -integrin-negative T cells. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Fibulin 5 interacts directly with elastin, and serves as a ligand for cell-surface integrins. Integrins require extracellular divalent cations to bind their matrix ligands, and low doses of chelators such as EDTA block these cell-matrix interactions (Brockdorff et al, 1998). As expected, control experiments demonstrated that integrin mediated migration of vascular smooth muscle cells to collagen was EDTA sensitive (Fig.…”
Section: Elastin Signals Via a Non-integrin G-protein Coupled Signalmentioning
confidence: 53%
“…Fibulin 5 interacts directly with elastin, and serves as a ligand for cell-surface integrins. Integrins require extracellular divalent cations to bind their matrix ligands, and low doses of chelators such as EDTA block these cell-matrix interactions (Brockdorff et al, 1998). As expected, control experiments demonstrated that integrin mediated migration of vascular smooth muscle cells to collagen was EDTA sensitive (Fig.…”
Section: Elastin Signals Via a Non-integrin G-protein Coupled Signalmentioning
confidence: 53%
“…FAK (23)(24)(25), as well as the focal adhesion kinase-related protein B (fakB) (26,27) and PYk2 (28,29) have been implicated. However, the precise mechanisms by which β2 integrins initiate activation of these tyrosine kinases are unknown.…”
Section: β2 Integrin Engagement Induces Activation Of Tyrosine Kinasesmentioning
confidence: 99%
“…EDTA, which is known as a chelator of different divalent cations (18,34), is able to bind both calcium and magnesium ions with almost the same affinity at neutral pH: log K ϭ 7.27 and log K ϭ 5.37, respectively; whereas EGTA in the presence of Mg 2ϩ is suitable for demonstrating calcium cation involvement alone (due to its higher association constant for calcium: log K ϭ 6.68 compared with magnesium log K ϭ 1.61 at pH 7) (35). -dependent lectins were not involved in NKL2/OSEC recognition, whereas integrins, which are the main adhesion molecules, of which activity is Mg 2ϩ dependent, might participate to NKL2 adhesion to organo-selective ECs.…”
Section: Distinct Divalent Cation Requirement For Nkl2 Adhesion and Smentioning
confidence: 99%